Avian malaria associations with British mosquitoes - Alves, R; Ricardo Orlando Neto Alves (2012)
Avian malaria (Plasmodium spp.) is a popular model system to study the ecology and evolution of parasite-host-vector interactions in the wild. These studies have historically focused mostly on the avian hosts and the malaria parasites. Knowledge regarding the role of vectors is essential to our understanding of these wild systems, but has only very recently started to accumulate. This thesis aimed to contribute to this field by assessing mosquito-malaria-host associations for British mosquitoes and the role of mosquito ecology in shaping these parasite systems in a British woodland study site, using molecular, field ecology and statistical modelling methodologies. From the 12 mosquito species or species groups found, I showed that the Cx.pipiens/torrentium mosquito group is likely to have a major role in avian malaria transmission in Great Britain, while Cs. annulata may be transmitting P. circumflexum. I also demonstrated a positive spatial association between mosquito density per host and avian malaria prevalence, in accordance with theoretical expectations for malaria transmission. Findings here provide evidence that avian malaria transmission in British woodlands is limited mainly to June-August, being preceded by relapse of previous infections or, alternatively, by maintenance of chronic blood parasitaemia through the colder months; this agrees with theoretical expectations and findings elsewhere for temperate climates. This thesis also described local-scale spatial heterogeneity and seasonal variation in adult mosquito abundance within a British woodland where avian malaria is endemic, with differing patterns found between species or species groups. Spatially, variation in adult mosquito abundance was associated with microclimatic and landscape variables such as distances to mosquito breeding sites, microclimate and canopy height; seasonally, variation in mosquito abundance was associated with temperature and rainfall, alongside calendar date. The heterogeneity in mosquito parameters and associations with environmental variables found at a site where avian malaria is endemic highlights the need to anticipate such complexity when trying to understand Plasmodium transmission. By doing so, we further extend the potential of these parasite systems to improve our knowledge regarding the ecology and evolution of parasite-host-vector associations.